Comparison of Curing Efficacy of Halogen and LED Polymerization Lamps Using Composite Materials of Different Polymerization Mechanism - P. Bradna; J. Froněk; L. Comba; D. Houšová (Czech Dental Chamber, 2009)
The objective was to compare efficacy of several types of halogen and LED polymerization lamps in curing restorative composite materials. Halogen lamps Heliolux DLX1 (Ivoclar Vivadent) and Megalux Fast Cure (MegaPhysik) and LED lamps DioPower (CMS Dental), Translux Power Blue (Heraeus Kulzer), BluePhase C8 (Ivoclar Vivadent) of a narrow spectral emission (group LED 1) and G-Light (GC, USA) and BluePhase G2 (Ivoclar Vivadent) of a broad spectral emission (group LED 2) were used. Curing efficacy was evaluated by measuring the composite hardness on the top irradiated and bottom not-irradiated surfaces of 2 mm thick specimens prepared from radically initiated dimethacrylate-based composite material Charisma (Heraeus Kulzer) and epoxy-based cationically polymerized composite material Filtek Silorane (3M ESPE). In curing of both composite materials a significant effect of the polymerization lamp on composite hardness and hence, polymerization degree was observed. The highest hardness of the composite material Charisma was found after polymerization with the halogen lamps and also BluePhase G2 of a broad spectral emission. With the epoxy-based Filtek Silorane the highest surface hardness was reached with both LED 2 and halogen lamps. In spite of limited number of polymerization lamps tested it seems obvious that the highest polymerization degree can be reached with polymerization lamps of broad spectral emission, such as high-power halogen lamps or LED lamps equipped with diodes emitting light in a short wavelength range.